Annelid Borings on Brachiopod Shells From the Upper Ordovician of Peru. A Long-Distance Co-migration of Biotic Partners - Villas, Enrique; Mayoral, Eduardo; Santos, Ana; Colmenar, Jorge; Gutiérrez-Marco, Juan Carlos (Frontiers in Ecology and Evolution, 2021)
The Recent planktonic larvae of the polychaete spionids are some of the most widespread and abundant group of coastal meroplankton worldwide. To study the possible co-migration of biotic partners and determine whether they were host-specific, the type of biotic relationship between hosts and borers of an Upper Ordovician Peruvian brachiopod collection from the Proto-Andean margin of Gondwana was re-exanimated and compared with material from Wales (Avalonia). The species list studied is composed of Colaptomena expansa (41%), Heterorthis retrorsistria (24%), Horderleyella chacaltanai (19%), Drabovinella minuscula (13%) and Dinorthis cf. flabellulum (3%) and coincides closely with that of the Dinorthis community described in the Caradoc series of North Wales. The borings attributed to these spionids have been identified as Palaeosabella prisca only present in the valves of Colaptomena expansa and Heterorthis retrorsistria. All the studied valves are disarticulated, with very low fragmentation and are randomly oriented in a context below the fair-weather wave base. The settling larvae would feed on their brachiopod host soft parts at an early stage, being the biotic interaction initially of the parasitic type. Since Palaeosabella borings from Peru and Wales are identical, as well as the species specificity of their producers with their brachiopod hosts, it can be concluded that the same spionid annelid species produced them. The Southern Westerlies current that connected the Proto-Andean margin of Gondwana with Avalonia must have been responsible for transporting the larvae of annelids and brachiopods in what had to be a successful biotic relationship over a great transoceanic distance.